2007
DOI: 10.1177/193229680700100113
|View full text |Cite
|
Sign up to set email alerts
|

Overview of Glycemic Control in Critical Care: Relating Performance and Clinical Results

Abstract: Background:Hyperglycemia is prevalent in critical care and tight control can save lives. Current ad-hoc clinical protocols require significant clinical effort and produce highly variable results. Model-based methods can provide tight, patient specific control, while addressing practical clinical difficulties and dynamic patient evolution. However, tight control remains elusive as there is not enough understanding of the relationship between control performance and clinical outcome. Methods:The general problem … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 72 publications
0
18
0
Order By: Relevance
“…This result also requires a level of adaptability from the TGC protocol that is not available in most published cases [66,[76][77][78].…”
Section: Discussionmentioning
confidence: 99%
“…This result also requires a level of adaptability from the TGC protocol that is not available in most published cases [66,[76][77][78].…”
Section: Discussionmentioning
confidence: 99%
“…Over 165 patients and 23,000 patient hours, it achieved an average blood glucose level of 5.8±1.2mmol/L with 61% of the time in the 4 -6.1mmol/L band [4]. This is the only approach adaptive to insulin sensitivity variation, as reflected in the hour to hour insulin-nutrition response to changing blood glucose levels.…”
Section: Introductionmentioning
confidence: 99%
“…Critically ill patients often experience stress-induced hyperglycemia and high levels of insulin resistance [1][2][3][4]. The increased counter-regulatory hormone and cytokine response stimulates endogenous glucose production and increases effective insulin resistance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This trial also had some of the tightest glucose control reported as compared to other studies e.g. [2,18,[23][24][25][26][27][28][29], indicating the potential of computational models to impact this field.…”
Section: Introductionmentioning
confidence: 70%